2016
DOI: 10.4236/jep.2016.71009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Analysis of Rural Medical Waste Management

Abstract: Objective: The aim is to understand the status of rural medical waste management and problems and to make recommendations. Methods: The questionnaire survey, interviews and comparative analysis are used. Results: Compared with urban medical waste management, rural medical waste management is weaker in classification, unified recycle, disposals, protect measures of related personnel, regulations and policies of awareness. Conclusion: It is recommended to improve policies and regulations of rural medical waste m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…township health centers and village clinics). Of the few papers that do exist, to our knowledge, even fewer adopt quantitative methods to investigate medical waste in rural primary institutions [ 3 , 17 ]. In addition, the geographic coverage of each of these papers is limited to just one province.…”
Section: Introductionmentioning
confidence: 99%
“…township health centers and village clinics). Of the few papers that do exist, to our knowledge, even fewer adopt quantitative methods to investigate medical waste in rural primary institutions [ 3 , 17 ]. In addition, the geographic coverage of each of these papers is limited to just one province.…”
Section: Introductionmentioning
confidence: 99%
“… 78 Nie and Wu used questionnaire survey, interview, and comparative analysis to evaluate the current situation of rural medical waste management in China, and pointed out that rural medical waste management is weak in classification, unified recycling, disposal, relevant personnel protection measures, regulations, and policy awareness. 79 Hong et al used LCC and LCA methods to quantify the environmental and economic impacts of three medical waste disposal options (ie, pyrolysis, steam sterilization, and chemical disinfection). 80 Narayanamoorthy et al evaluated the bio-medical waste disposal based on comprehensive weighting method and hesitant fuzzy MOOSRA, and the results showed that autoclaving is the best choice for bio-medical waste treatment.…”
Section: Related Research On the Management And Evaluation Of Medical...mentioning
confidence: 99%
“…Bentley [1] classified and interpreted the cost of medical waste disposal in various US agencies, and made recommendations to guide the reduction of medical waste disposal costs. In order to reduce the cost of medical waste management in hospitals, Almuneef [2] targeted An internal medical waste management plan was proposed; Zhang Ni [3] used questionnaires to investigate the types of medical waste and related expenditures generated by medical institutions in Dongcheng District, Beijing, in order to explore scientifically reduce the cost of medical waste disposal, reduce the burden on medical institutions, and reduce The patient's medical expenses are provided. At the same time, many scholars use game theory for research in the medical field.…”
Section: Introductionmentioning
confidence: 99%